Using the quality by design (QbD) approach to optimize formulations of lipid nanoparticles and nanoemulsions: a review - Cunha, Sara (2021)
Quality-by-design (QbD) approach has been applied to optimize lipid-based nanosystems formulations, including solid lipid nanoparticles (SLN), nanostructured lipid carriers (NLC) and nanoemulsions, besides being increasingly requested by regulatory authorities. Different mathematical models and statistical tests have been used, with similar conclusions regarding the parameters that influence the physical features of the resulting nanosystems. These include, variations in composition (e.g. lipid(s) and/or emulsifier(s)) and manufacturing parameters (e.g. emulsification rate and/or time, sonication amplitude and/or time, and homogenization pressure and/or cycles). These are critical parameters that influence nanoparticle/globule mean size, polydispersity index, zeta potential, drug encapsulation efficiency and in vitro drug release. This review addresses the concepts and applications of QbD for the development of lipid-based nanosystems, reporting successful examples published in the last 2 years. Although, some limitations have been identified, it is expected that in the upcoming years the application of QbD in pharmaceutical development will be an established approach.